Gestão do Conhecimento no Centro de Educação e Formação Profissional Integrada: diagnóstico e recomendações - Oliveira, Lara Filipa Figueiredo de (2021)
Any company or organization must have as one of its purposes, to improve its performance by exploring the knowledge acquired over the years of operation in the market. This knowledge includes, in addition to the results of operational activities, a comprehensive understanding of the coexistence between people and processes. The work developed and described in this document, intends to summarize the research carried out at Center for Integrated Vocational Education and Training (CEFPI) with the aim of improving Knowledge Management. Within the scope of the case study described, several techniques were used to collect data such as questionnaires and interviews with employees of the organization for an in-depth study. In addition to the questionnaires and interviews, a study will also be carried out through a document analysis that will be provided by the same organization. Subsequently, the collected data were analyzed with the aid of different instruments. As a result, it was possible to create a specific model of knowledge management applicable to the organization under study (CEFPI), but it could be useful or adapted for other organizations as well. As a result, it was possible to obtain a set of recommendations and diagnosis in this area of knowledge management.